URBAN FURNITURE DESIGN - Nikoljski Panevski Elena; Emilija Tashkova (Ss. Cyril and Methodius University in Skopje, Faculty of Design and Technologies of Furniture and Interior in Skopje, 2019)
For the purpose of this work exterior furniture and urban equipment or set of exterior furniture is designed for arranging urban area (park, square). By analyzing this type of furniture and its needs, there comes the need for designing several different pieces of furniture, including: chairs (seating for one), two- person benches, three-person benches, flower pots, ambient lighting and bins. By analyzing outdoor furniture and its needs from material aspect, one can realize that there are certain reasons why there is use of oak wood for the first model of outdoor benches, and thermo wood for the second model of outdoor benches. This paper analyzes the benefits of using these types of wood. In the process of designing, one starts from the square as a geometrically most stable shape, and its further development and integration in the shape of the outdoor furniture. The anthropometric standards researched for this type of furniture, as well as the choice of material, should meet the requirements and needs of the desired look. The ultimate goal is to get a quality sitting and living outdoor in which the human factor is very important. Through better understanding of the parameters of ergonomics, the designer can improve the health and safety of the furniture users. Actually, the obligation and the task of the planner is to constantly monitor research in the field of ergonomics in order to implement, maintain and improve the design of furniture.
Keywords: outdoor bench; lighting; litter bins; pot; construction; wood coatings